Understanding the recurrence of amoebic liver abscess in South Bihar: a clinical case report - Mahto, Binay Kumar; Kumar, Sanjay; Kumar, Sant; Kumari, Rashmi; Shreya; Kushwah, Hotam Singh; Kumar, Ashish; Tumram, Akshay Shamrao; Shekhar , Shashank (International Journal of Research in Medical Sciences, 2025)
Amoebic liver abscess is a common disease condition in some parts of India, including Bihar, due to the higher prevalence of amoebiasis and habitual consumption of toddy (tari). Recurrence of amoebic liver abscess is not uncommon; although it is underreported with only a few previous reports. In this study, a patient from South Bihar presented with three subsequent episodes of amoebic liver abscess over a period of six years. Possible considerations for these recurrences have been explored, which revealed the fact that recommended full-dose treatment with metronidazole followed by a luminal amebicide agent to eradicate intestinal amoebic colonization is necessary for effective treatment of an amoebic liver abscess.